Conservation, Creation, and Evolution: Revising the Darwinian Project - Gennady Shkliarevsky (Journal of Evolutionary Science, 2019)
There is hardly anything more central to our universe than conservation. Many scientific fields and disciplines view the law of conservation as one of the most fundamental universal laws. The Darwinian model pivots the process of evolution on variability, reproduction, and natural selection. Conservation plays a marginal role in this model and is not really universal, as the model allows exceptions to conservation, i.e. non-conservation, to play an equally important role in evolution. This anomalous role of conservation in the Darwinian model raises questions: What is the reason for this anomaly? Is conservation really universal, as we tend to believe or is it not, as the Darwinian model suggests? This contribution proposes a new model of evolution that focuses on levels of organization, rather than of species, organisms, or populations. It argues that conservation is central to evolution. Not only does this new model restores the universal status of conservation but it also makes possible to resolve some outstanding problems and controversies that continue to plague the Darwinian model. The article tries to advance the broad Darwinian project that seeks to explain the process of evolution as a product of the spontaneous processes in nature.
Keywords: Conservation